Accident Prediction Model By Relating Integrated Design Consistency Model - Prasetijo, Joewono (International Journal of Integrated Engineering, 2020)
The number road accident kept rising in every year in Malaysia. In early 2016, Johor has been mentioned as the among highest-ranking road accident at hazard road locations. The main accidents occur are a road accident with passenger cars, road accident with other motorcycles and single-motorcycle road accidents. Furthermore, the problem road accident on hazard road location are still unsolved, especially for main road accident types of vehicle; motorcycles and cars. The study location segments were selected at Johor Federal Route 50; KM1- KM5. Therefore, this study using an accident prediction model by relating integrated design consistency model, through a comprehensive speed characteristic using a global positioning system and based on an operating profile to develop a continuous speed profile between motorcycles and cars and to determine design consistency models. Poisson model is used to relate road design consistency models and accident rates to evaluate the impact of design consistency with road safety.